Alkali reduction of ribonucleic acid in microbial biomass protein on coconut residue - Navera, Theresa Ann Realubit; De Leon, Sonia Y. (1992)
The study attempted to determine the initial ribonucleic acid (RNA) and true protein content of two Microbial Biomass Proteins (MBP) grown on the solid substrate, coconut (Cocos nucifera) residue or sapal and, to measure any resultant change in RNA and protein levels of the two MBPs after nucleic acid reduction. The results of the study showed that the RNA content of MBP grown on coconut residue could be greatly reduced by means of alkali extraction. Incubation of MBP at pH 10-10.5 and 80°C for 4 hours successfully reduced experimental figures of RNA from 9-13% to negligible amounts. However, these figures are estimates due to limitations inherent in the methodology. The initial true protein values for the samples with the more consistent values were 61.6 to 66.22%. The final true protein values were reduced although they varied widely from each other. It is suggested that further experiments using other quantitative methods should be conducted to establish the effect of RNA reduction on the true protein values.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut products; Single cell protein